Maintained partial protection against Streptococcus pneumoniae despite B‐cell depletion in mice vaccinated with a pneumococcal glycoconjugate vaccine. Issue 1 (28th December 2021) - Ercoli, Giuseppe; Ramos‐Sevillano, Elisa; Pearce, Emma; Ragab, Sara; Goldblatt, David; Weckbecker, Gisbert; Brown, Jeremy S
Abstract: Objectives: Anti‐CD20 monoclonal antibody therapy rapidly depletes > 95% of CD20 + B cells from the circulation. B‐cell depletion is an effective treatment for autoimmune disease and B‐cell malignancies but also increases the risk of respiratory tract infections. This effect on adaptive immunity could be countered by vaccination. We have used mouse models to investigate the effects of B‐cell depletion on pneumococcal vaccination, including protection against infection and timing of vaccination in relation to B‐cell depletion. Methods: C57BL/6 female mice were B‐cell depleted using anti‐CD20 antibody and immunized with two doses of Prevnar‐13 vaccine either before or after anti‐CD20 treatment. B‐cell repertoire and Streptococcus pneumoniae –specific IgG levels were measured using whole‐cell ELISA and flow cytometry antibody‐binding assay. Protection induced by vaccination was assessed by challenging the mice using a S .  pneumoniae pneumonia model. Results: Antibody responses to S. pneumoniae were largely preserved in mice B‐cell depleted after vaccination resulting in full protection against pneumococcal infections. In contrast, mice vaccinated with Prevnar‐13 while B cells were depleted (with > 90% reduction in B‐cell numbers) had decreased circulating anti– S. pneumoniae IgG and IgM levels (measured using ELISA and flow cytometry antibody binding assays). However, some antibody responses were maintained, and, although vaccine‐induced protection against S. pneumoniae infection was impaired, septicaemia was still prevented in 50% of challenged mice. Conclusions: This study showed that although vaccine efficacy during periods of profound B‐cell depletion was impaired some protective efficacy was preserved, suggesting that vaccination remains beneficial. Abstract : Timing of pneumococcal vaccination in B‐cell–depleted patients is critical for vaccine efficacy. This study shows that, although full protection can only be ensured by vaccinating mice before depletion, vaccination during/after depletion can also provide a degree of immunity against S .  pneumoniae .